Deer Flies, Yellow Flies and Horse Flies, Chrysops, Diachlorus, and Tabanus spp. - Jason M. Squitier (EDIS, 2003)
The family Tabanidae, commonly known as horse flies, and deer flies, contains pests of cattle, horses and humans. In Florida there are 35 species of Tabanidae that are classed as economically important. Horse flies are in the genus Tabanus, deer flies are in the genus Chrysops. The yellow fly, Diachlorus ferrugatus (Fabricius), is known as a fierce biter in Florida. Like mosquitoes, it is the female fly that is responsible for inflicting a bite. The males are mainly pollen and nectar feeders. Tabanids are most likely encountered in hot summer and early fall weather. They are active during daylight hours. This document is EENY-028, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April, 1998. Revised: November 2003.